The service quality and satisfaction of smart policing in the UAE - Maryam Ekaabi; Khalizani Khalid; Ross Davidson (Cogent Business & Management, 2020)
The purpose of this paper is to investigate the multidimensional constructs of smart policing service quality, and the impact of these dimension on the satisfaction levels of UAE residents. An online survey was conducted using a sample of 230 respondents and analyzed using structural equation modeling. The findings of this study confirm that integrity and serviceability have a significant and positive impact on satisfaction. When hedonic dimensions are controlled, it was found that integrity, transparency, responsivity, interactivity, and serviceability are significant predictors of satisfaction. When utilitarian dimensions are controlled, only integrity, transparency, interactivity and serviceability are significant related to satisfaction. This study contributes to the policing and service quality research because limited studies demonstrate how smart policing service quality dimensions drive satisfaction. This research extends beyond current e-service quality models by addressing the importance of utilitarian dimension in police services quality. Such factors and their strategic relation to satisfaction are often overlooked in the public sector for the sake of maintaining long term relationships with residents; a sector in which users are believed to be mostly driven by hedonic motives.
Keywords: 650; satisfaction; police service quality; smart policing; UAE